Perancangan dan Implementasi Sistem Informasi Manajemen Panti Asuhan Menggunakan Pemrograman Java Netbeans - Yuliana Monika Liwu; Kristianus Jago Tute; Benediktus Yoseph Bhae (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
The role of information technology in the era of digitalization as it is today is very important to support all forms of activity. One of the areas of research being studied is the social sector, the Orphanage. Bhakti Luhur Orphanage Ende Branch is one of the orphanages in Ende Regency which is moved to help serve children with special needs. The problem in this study is that the data processing of the orphanage is still done conventionally, namely by recording in a ledger so that there is accumulation of data which causes difficulties in searching for certain data and the quality of information and data is not presented quickly and accurately. The purpose of this research is to design and implement an orphanage management information system using Java Netbeans programming and MySQL database. Data collection techniques by conducting interviews, direct observation and study documentation. The system development method uses the Fountain Model with system testing using black box testing and user testing. From the results of blackbox testing, it shows that the results are in accordance with the design and some functionalities are running well. Meanwhile, based on the results of non-functional testing through questionnaires from 7 respondents from the Bhakti Luhur Orphanage at Ende Branch, the majority of this system is acceptable for users, through an indication of the average percentage of 88% and 85% and overall can be categorized as "Decent".